Tumors and coagulation - Brenneisen P., Mercedes (1971)
Were performed in 53 subjects , the following tests: clotting time by the Lee- White methods and I recalcified plasma ; bleeding time , by the method of clot, quantitative method ; determination of prothrombin , Factor I, Factor VIII , fibrinolytic activity , generation of thromboplastin with the respective corrections and loop test . Of this group, 38 patients corresponded to the National Institute of Neoplastic Diseases , carrying mostly disseminated lymphomas (29 ) and other malignancies ( Table A-1 ) (9 cases). The ages of the patients ranged from 7 to 72 years , mean 37 years , 26 males and 12 females. As a control served fifteen normal subjects whose ages ranged between 19 and 30 with 8 male and 7 female. The results were expressed in 12 graphs and tabulated in 5 frames to differentiate first between the control group and total neoplasms , then between lymphomas and other malignancies , and finally , between the states of " Hypercoagulability " and " Hypercoagulability " with normal values ​​. The results are discussed and it is concluded that there are alterations in coagulation factors , both more and less in patients with disseminated malignancies.